Simulation and performance of multiple input multiple output orthogonal frequency division multiplexing wireless local area network 802.11a - Satya Nand, Rajan Ratti (2006)
802.11a and Hiperlan/2 are two major WLAN standard developed by the ETSI and IEEE respectively to meet demands for a mobile with high bandwidth data, voice and video access. This research studies the IEEE 802.11a standard has it is predicated by the telecommunication industry, to be next leading, advance and important WLAN technology. This system is expected to provide channel adaptive data rates up to 54 Mb/s in a 20 MHz channel spacing in the 5 GHz radio band. An overview and description of IEEE 802.11a is presented. Literature review on past white papers and journal research data is referred before modelling the IEEE 802.11a physical layer. Using Simulink in conjunction with the Matlab software the simulated physical layer and BER versus Eb/No performance results is presented for each defined transmission mode 1 to mode 8 by the IEEE 802.11a standard. The simulated physical layer consists of a transmitter and receiver under a real WLAN mobile link channel. This mobile link channel consists of AWGN, Path Loss, Rician and Rayleigh Fading. Computer simulations with different delay spread values are carried out and the achievable performance with BER floor value of 10-5 in a multipath environment is shown. In which the results show that with the increase of delay spread value there is a graceful degradation of achievable performance. This may be applied to mitigate multipath effect using OFDM based transmission. Further performance improvement is done by modelling a MIMO extension for the existing design. The MIMO design consists of a 2 transmit antenna and 2 receive antenna extended to OFDM design. Results have shown that an average of 8% improvement of Eb/No at BER floor value of 10-5 for all modes with common modulation format and code rate. The research will be applicable in studying and comparing WLAN systems that do not deploy OFDM or MIMO-OFDM in terms of achievable performance.